Revolutionizing Agricultural Disease Detection: Conv2D And Unet Models For Chilly Leaf Analysis - D.Prabhu, Golda Dilip (Cuestiones de Fisioterapia, 2025)
Significant economic losses may happen as a result of the challenges faced by the agriculture industry in tracking down and managing crop diseases. A number of diseases, including leaf spot, powdery mildew, and bacterial wilt, can severely damage chilli crops (Capsicum annuum).